Model or Mould? A Challenge for Better Traceability - Morris, S. J.; Gotel, O. C. Z. (International Workshop on Modeling in Software Engineering (MISE'07: ICSE Workshop 2007), 2007)
This paper examines the notion of the model as it may be used in software engineering via the definition of a series of progressively more complex relationships between the modeller, the model and what is modelled. A gradual historical development is identified where the purpose of the model changes from its representation of a pre-existing subject to its action as a precedent and a definition for some subsequent artifact that is its object. The notion of a composite model type, or mould, combining both purposes is made explicit. Its implications for traceability in multi-model processes are being investigated.